2,2 '-anhydro-2 '-C-methyl-1-(beta-D-arabino-furanosyl)uracil (2,2 '-anhydro-2 '-C-methyl-uridine) - Jenkinson, S; Jones, N; Moussa, A; Stewart, A; Heinz, T; Fleet, G; Watkin, D (2007)
The structure of anhydro-2′-C-methyl-uridine, C10H12N2O5, is firmly established by X-ray crystallography, with the sugar adopting a furan-ose ring. The absolute stereochemistry is inferred from the use of 2-C-methyl-d-arabinose as the starting material. The mol-ecules are linked by two conventional O - H⋯O hydrogen bonds, and one C - H⋯π hydrogen bond. © 2007 International Union of Crystallography. All rights reserved.